An Electronic Control Unit for Thermoelectric Cooling - Sanver, Ufuk; Yavuz, Erdem; Eyupoglu, Can (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2019)
Due to their efficient operation in small volumes, Thermoelectric Coolers (TECs) have a wide usage in cooling applications, and are preferable wherever usage of compressor-based cooling systems is hard. In this study, a control unit for thermoelectric cooling modules has been designed and implemented based on a microcontroller. The designed system allows users to specify the threshold values for thermoelectric coolers to operate on. The microcontroller drives the TEC using a pulse width modulation (PWM) technique via a MOSFET as a switching component. Adopting a PWM-based control technique makes it possible to manage the speed and energy consumption of the TEC system.